Prevalence of iron deficiency with or without anemia among medical staff in Tishreen University Hospital (Latakia University Journal -Medical Sciences Series, 2022)
Background: Iron deficiency without anemia (IDWA), the most prevalent nutritional deficiency worldwide, affects young women of reproductive age. There are no evidence-based recommendations to screen for iron deficiency in non-anemic patients, even though symptoms may be present.Aim: In this study, we aim to explore the prevalence of iron deficiency, with and without anemia, among medical staff females at Tishreen University Hospital.Materials and Methods: This was an observational descriptive cross-sectional study conducted at Tishreen University Hospital, Lattakia, Syria during the period between July 2019 and July 2020. Three hundred eighty medical staff females doctors and nurses) working at Tishreen University Hospital between the ages of 20 and 50 years were randomly sampled. Blood samples were collected for complete blood count (CBC) values and serum ferritin determination. The subjects were classified as having IDWA (hemoglobin (Hb) ≥ 12 g/dL and serum ferritin